Effectiveness of guided writing in responding simple questions in daily life at 4th grade elementary students - Gaffar, Muhammad Andriana; Gumelar, Wahyu Satya; Syafitri, Nesyza Nurdiyani (Journal of Research in Instructional, 2025)
This study delves into the effectiveness of guided writing in enhancing fourth-grade students' ability to respond to simple questions in daily life contexts. Using a pre-experimental design with a one-group pre-test and post-test, the research was carried out at an elementary school in Pameungpeuk Bandung with 42 participants. The results demonstrated a significant improvement in students' writing skills. In the post-test, 21.4% of students reached an excellent classification, and 45.2% achieved a reasonable classification, a marked improvement from the pre-test, where none had done so. Students also showed better grammatical accuracy, sentence organization, vocabulary use, and confidence in writing. Guided writing emerged as a practical instructional approach, equipping young learners with the tools to strengthen their grammar, coherence, and motivation in writing. These findings underscore the practical implications of structured writing instruction, which can significantly enhance students’ ability to communicate effectively in written English, and it begins with effectively responding to simple questions in daily life.